Municipality (State Treasury) in the class of persons entitled to restitution of expropriated real estate - Terlega, Jakub (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2014)
The paper aims to describe a legal problem in the application of rules governing the restitution of expropriated real estate - namely a situation in which one of the entities entitled to restitution of expropriated property, turns out to be a municipality or the State Treasury, as a statutory heir of the previous owner. Usually, the State Treasury, as one of the heirs, does not have an interest in supporting the request for the restitution of expropriated property.The author is of the opinion that the proper interpretation of rules governing the restitution of expropriated real estate requires the assumption that whenever one of the statutory heirs turns out to be the State Treasury, consent to request a restitution of expropriated real estate by the State Treasury is not required. In the absence of such an agreement, the competent authority is obliged to grant the restitution of the expropriated real estate to all heirs.